Pengaruh Pengasuhan Otoritatif Orangtua dan Motivasi Belajar terhadap Hasil Belajar pada Siswa Kompetensi Keahlian Pemasaran SMK Negeri Kota Padang - Ristiliana Ristiliana; Marwan Marwan (Jurnal Kajian Pendidikan Ekonomi, 2014)
This study aims to reveal the effect of authoritative parenting to student’s learning motivation, the effect of learning motivation to students’s learning outcomes and the effect of authoritative parenting to students’s learning outcomes on Marketing Competency Students of State Vocational High School in Padang. This research is descriptive associative which explain an event or phenomenon that has occurred and this research also conducted to see the influence between these variables. The population in this study were all students are concentrated on marketing competency of state vocational High School in Padang consisting of class X , XI and XII from 637 students, and after selected by Proportional Random Sampling technique, so that the sample in this study consist 246 students. The data analysis technique used in this study is path analysis and the test of hypothesis using the F test and t test. Based on the result of the study can be concluded that: 1) The authoritative parenting have a significant effects on the learning motivation in Marketing Competency Students of State Vocational High School in Padang. The level of students' learning motivation is influenced by whether or not the authoritative parenting implemented by parents. 2) The learning motivation have a significant effects on the learning outcomes in Marketing Competency Students of State Vocational High School in Padang. Its influence, both directly and indirectly through the authoritative parenting. However, greater direct influence of motivation toward learning outcomes are compared through authoritative parenting. 3) ) The authoritative parenting have a significant effects on the learning outcomes in Marketing Competency Students of State Vocational High School in Padang. Its influence, both directly and indirectly through the students' learning motivation. However, authoritative parenting have a greater influence on learning outcomes indirectly through student’s learning motivation. Based on the conclusions above, can be suggested the following points are to the students of Marketing Competency of State Vocational High School in Padang to receive the positive authoritative parenting students can do well with frequent communication with parents, Open on your parents about what occurs in learning. In addition to increasing the motivation of learning, students are expected to diligently repeat again the lessons at home and to all parents of students to complete all student learning facilities. For parents of students are expected to be involved in their learning such as supervise the student learning activities, ask about the student learning difficulties, and involved in providing solutions to the problems facing student learn. Teachers also suggested that more attention to the development of students learning by working on the parents. Keywords: Authoritative Parenting, Learning Motivation and Learning Outcomes